Enhancing Potato Production using Tuberlet Technology (92-PT-27) in Changing Climatic Circumstances in Bihar - Sima Sinha, Parasnath and Shambhu Kumar, (Indian Journal of Extension Education, 2018)
The objective of the study was to compare the potato production in two different agro climatic zones of Bihar state bycomparisons between tuberlet (92-PT-27) / true potato seeds, high yielding potato varieties (kufri Ashoka) and farmers'variety (chandramukhi in Madhepura, sathi in Supaul and jyoti jalandhar in Banka) using true potato seed technology andevaluating for yield and against major disease, late blight. This trial was conducted on a few selected farmers' field inSupaul, Madhepura and Banka districts of Bihar state during three consecutive years 2012, 2013 and 2014. Raghopur,Basantpur and Saraigarh were the blocks selected from Supaul district; Uda Kishanganj, Murliganj and Kumarkhandfrom Madhepura district and Banka, Amarpur and Baunsi blocks were selected from Banka district. From every block thatwas selected, 10 potato growers were chosen, making a total sample size of 90 potato growers. Selections were done byrandom sampling. It was found that average yield of 92-PT-27 was the highest at all three locations as compared to highyielding varieties and farmers' variety. The benefit cost (BC) ratio was 2.86 for 92-PT-27, which was substantially higherthan 1.87 of Kufri Ashoka and 1.63 of local check. The results reveal that the 92-PT-27 (tuberlet) has a great potential forcommercial production of potato. The TPS technology may serve as a potential alternative to mitigate the problem on nonavailabilityof quality seeds.